Unleashing the potential of evolutionary swarm robotics in the real world - Duarte, M.; Costa, V.; Gomes, J.; Rodrigues, T.; Silva, F.; Oliveira, S. M.; Christensen, A. L. (2016 Genetic and Evolutionary Computation Conference, GECCO 2016 Companion, 2016)
We provide a summary of our real-world experiments with a swarm of aquatic surface robots with evolved control. Robotic control was synthesized in simulation, using of- fline evolutionary robotics techniques, and then successfully transferred to a real swarm. Our study presents one of the first demonstrations of evolved control in a swarm robotics system outside of controlled laboratory conditions.